La Flora Común es la Flora Medicinal - Brent Berlin; Elois Ann Berlin (Revue d'ethnoécologie)
This essay draws a definitive distinction between special or secret knowledge and popular [folk or common] knowledge of the medicinal plant species that form the core of the empirical herbal medicine of the Tzeltal and Tzotzil of the Chiapas Highlands. We intend to demonstrate that the Maya herbolaria consists principally of the common flora of the region. In addition, these species are recognized by the general population, not only by specialists or individuals who identify as traditional doctors. We can conclude that the body of Tzeltal-Tzotzil herbal knowledge is, then, the folk medicine of the Maya in the same sense as we may speak of Mexican folk medicine. The herbolaria of the Maya does not consist of sacred information nor secret knowledge. The system is public and merits study by anthropologists, ethnobotanists, students of ethnomedicine, and laboratory analysis, always in close collaboration with the Mayan communities, with regard to methods of preparation and administration, bioactivity, toxicity, and quality control.